Cocoon morphology of the cockroach-hunting apoid wasp Ampulex compressa (Fabricius) (Hymenoptera, Ampulicidae). - Buys, Sandor Christiano (Contributions to Entomology = Beiträge zur Entomologie, 2015)
The cocoon morphology of the cockroach-hunting apoid wasp Ampulex compressa (Fabricius, 1781) (Hymenoptera: Ampulicidae) is described, based on five cocoons examined under binocular microscope. This is the first detailed description of cocoons of Ampulicidae. The examined material was obtained from a stock of wasps maintained in laboratorial conditions, using specimens of Periplaneta americana (Linnaeus, 1758) (Blattaria: Blattidae) as host. The cocoon is constructed within the exoskeleton of the host and has three capsules. The external and middle capsules are formed by structurally distinct types of silken threads, whereas the internal capsule is formed by a brittle substance, without distinguishable silken threads. The cocoons of A. compressa are morphologically distinct from those of the related families Sphecidae and Crabronidae and, perhaps, its complex and reinforced structure represents a kind of mechanic barrier that function in association with the antimicrobial oral secretions of the larvae as a protection against antagonistic microbes. Keywords Immature stage, larvae, life history, taxonomy, biology, Sphecidae, Crabronidae.